DEPENDENCE ON FOREST PRODUCTS BY PEOPLE LIVING AROUND PROTECTED FORESTS IN THAILAND : SUSTAINABLE RELATIONSHIP OR FOREST - EOCOSYSTEM DESTRUCTION ? - Boonchote, Thawatchai; Pasandhanatorn, Vannawipha (วารสารวนศาสตร์ไทย, 2022)
Forest-ecosystem disturbance caused by non-timber forest product (NTFP) harvesting by local people is a controversial issue. Conflicts between local people and the government due to NTFP collection, occur in several protected forests in Thailand. The main purpose of this study was to explore people's collection and use of NTFPs at 2 sites: site 1; consisted of 4 villages in the buffer zone of a protected forest, and site 2 was a village adjacent to a reserved forest. Additionally, institutional arrangements were also investigated. The results indicate that some NTFPs, i.e. various types of mushroom, bamboo shoots and Phak Wan (Melientha suavis Pierre) are popular and heavily collected by local people. Thus the degree of forest ecosystem disturbance may be beyond the natural carrying capacity, particularly for highly priced products. To minimise the negative effects on forest ecosystem disturbance due to NTFP collection, co - operation from local people is imperative. Management techniques that utilise the insights gained from community - relation programs such as those at Site 2, are also needed. Above all, officials should have a positive attitude towards the villagers’ livelihood. Flexibility in dealing with local people is also considered important.